Black tea and D. candidum extracts play estrogenic activity via estrogen receptor α-dependent signaling pathway - Wang, Yongsen (Am J Transl Res, 2018)
In recent years, phytoestrogens have been shown as useful selective estrogen receptor modulators. The estrogen-like effects of black tea (BT) and D. candidum (DC), as well as the combination of the two herbs, have remained largely elusive. This study aims to investigate the phytoestrogenic effect of BT and DC extract, and the possible mechanism. The effects on T47D (ER+ cell line) proliferation were evaluated by using MTT assay. The S phase proportion of ER+ cells was determined by using flow cytometry. The estrogen antagonist ICI 182,780 was applied to block the ER function. The activation of ER-mediated PI3K/AKT and ERK signal pathways were observed by using western blot. Expression of ERα and PGR, as well as PS2 and Cyclin D1 were detected by using western blot and real-time quantitative PCR. Firstly, our results found that BT and DC extracts promoted cell proliferation in ER-positive cells, and this effect was ER-dependent. Besides, BT and DC extracts increased the S-phase cell number. Next, PI3K, AKT and ERK pathways below ER were activated by phytoestrogen treatment, and this activation was blocked by the ER antagonist. Moreover, prolonged BT and DC treatments increased the expression of ESR1 and PGR. Consistently, the mRNA levels of not only ESR1 and PGR but also estrogen-dependent effectors ps2 and cyclin D1, were increased by phytoestrogens and blocked by ICI 182,780. Taken Together, BT and DC extracts have phytoestrogenic effects, and this may provide new ideas and experimental basis for the development and application of phytoestrogens.